Defects in maintenance of mitochondrial DNA are associated with intramitochondrial nucleotide imbalances - Ashley, N; Adams, S; Slama, A; Zeviani, M; Suomalainen, A; Andreu, A; Naviaux, R; Poulton, J (Oxford University Press, 2007)
Defects in mtDNA maintenance range from fatal multisystem childhood diseases, such as Alpers syndrome, to milder diseases in adults, including mtDNA depletion syndromes (MDS) and familial progressive external ophthalmoplegia (adPEO). Most are associated with defects in genes involved in mitochondrial deoxynucleotide metabolism or utilization, such as mutations in thymidine kinase 2 (TK2) as well as the mtDNA replicative helicase, Twinkle and gamma polymerase (POLG). We have developed an in vitro system to measure incorporation of radiolabelled dNTPs into mitochondria of saponin permeabilized cells. We used this to compare the rates of mtDNA synthesis in cells from 12 patients with diseases of mtDNA maintenance. We observed reduced incorporation of exogenous α 32P-dTTP in fibroblasts from a patient with Alpers syndrome associated with the A467T substitution in POLG, a patient with dGK mutations, and a patient with mtDNA depletion of unknown origin compared to controls. However, incorporation of α 32P-dTTP relative to either cell doubling time or α 32P-dCTP incorporation was increased in patients with thymidine kinase deficiency of PEO as the result of TWINKLE mutations compared with controls. The specific activity of newly synthesized mtDNA depends on the size of the endogenous pool diluting the exogenous labelled nucleotide. Our result is consistent with a deficiency in the intramitochondrial pool of dTTP relative to dCTP in cells from patients with TK2 deficiency and TWINKLE mutations. Such DNA precursor asymmetry could cause pausing of the replication complex and hence exacerbate the propensity for age-related mtDNA mutations. Because deviations from the normal concentrations of dNTPs are known to be mutagenic, we suggest that intramitochondrial nucleotide imbalance could underlie the multiple mtDNA mutations observed in these patients.